A proteção dos direitos fundamentais de crianças e adolescentes brasileiros expostos aos ‘jogos’ de desafio na internet - Chaves, Elisa Viana Dias (2021)
The present study intends to analyze the vulnerability of children and adolescents in the face of dangerous and harmful content existing in the so-called challenge 'games', verifying the action of the actors in charge of integral protection in Brazil for the promotion and protection of fundamental rights of children and adolescents in this context. context, in order to finally present alternatives for the realization of the best interest of the child. In the so-called 'games' of challenge, practitioners are often induced to self-mutilation, self-exposure to risk, and even suicide. Such behaviors have become a worldwide concern in view of their rapid dissemination through the internet, which is why the study of the subject is relevant, when it investigates whether it is possible to affirm that family, society and the State are effectively fulfilling their duties in the promotion and protection of the fundamental rights of these players, and then, verifying the shortcomings of the current system, present alternatives to reconcile technological advances and their risks, with the Doctrine of Integral Protection. For its development, the present work was based on Manuel Castells, Josiane Rose Petry Veronese, Rosane Leal da Silva and Lynn Rosalina Gama Alves, adopting the deductive method of approach, while the method of procedure used is the monographic and comparative, the the first will be used to analyze examples of challenge 'games' and their risks, which will allow the approximation between theory and practice, while the second will be used insofar as experiences carried out in member countries of the European Union to promote integral protection will be verified of children and adolescents who participate in challenge games, verifying whether these practices could be replicated in Brazil. The documentary technique was used, with the elaboration of files and summaries based on the readings carried out for the study of the theme, as well as the technique of direct observation of challenge ‘games’, especially those that are published on the Youtube website. The false impression of being prepared by "digital natives" for safe navigation is deconstructed when their lack of maturity is verified, as well as the free circulation of harmful and illegal content in the online environment, in this scenario it is up to those in charge of integral protection to make the internet a safer environment, promoting the fundamental rights of children and adolescents and a dignified life, in which they are allowed the free and protected exercise of these rights.